2020
DOI: 10.1093/icvts/ivaa229
|View full text |Cite
|
Sign up to set email alerts
|

Midterm result of custom-made iliac branch device for common iliac aneurysm with and without abdominal aortic aneurysm

Abstract: OBJECTIVES Although commercial iliac branch devices offer a new and valid endovascular approach to treating iliac aneurysm and effectively preserve antegrade flow of the internal iliac artery, their use may not be suited for all types of challenging anatomy, especially isolated common iliac artery aneurysm. Our custom-made iliac bifurcation device has a unique design and excludes both combined and isolated iliac branch aneurysm. This study validated the efficacy and safety of the custom devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…When commercial IBDs are deemed inappropriate for CIAA management, custom IBDs are available as an alternative. Although a restricted number of studies [ 29 , 30 ] have provided evidence regarding the safety and effectiveness of this method, there is a scarcity of substantiating evidence to support its application.…”
Section: Discussionmentioning
confidence: 99%
“…When commercial IBDs are deemed inappropriate for CIAA management, custom IBDs are available as an alternative. Although a restricted number of studies [ 29 , 30 ] have provided evidence regarding the safety and effectiveness of this method, there is a scarcity of substantiating evidence to support its application.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach, when patients with challenging anatomy require iliac aneurysm treatment, could be the use of a custom-made iliac branch device. Huang et al found non-inferior results when comparing their custom-made devices to commercial devices in a cohort of 46 patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that differences in peri-operative or late performances among the grafts may exist, but we did not have enough data in this study to perform subgroup analyses. Nonetheless, to our best knowledge, no relevant differences were detected among the current IBDs regarding patient outcomes [ 12 , 18 ]. Finally, the low event rate did not make the evaluation of the adjusted risk factors for the primary and secondary endpoints possible.…”
Section: Discussionmentioning
confidence: 99%